Zircon double-dating, trace element and O isotope analysis to decipher late Pleistocene explosive-effusive eruptions from a zoned ocean-island magma system, Ascension Island - Scarrow, Jane H.; Schmitt, Axel Karl; Danišik, Martin; Chamberlain, Katy J.; Davies, Bridie V.; Rushton, Jeremy; Brown, Richard J.; Barclay, Jenni (Quaternary science reviews, 2023)
In this first detailed study of zircon from Ascension Island, South Atlantic, we take a novel approach combining trace element and O isotope compositional data with double-dating (disequilibrium 238U-230Th and (U-Th)/He) to decipher timescales and dynamics of magmatic processes. The Echo Canyon (EC) sequence comprises small-volume explosive-effusive eruptions of trachyte that tapped a compositionally zoned magma system. Associated volcanic hazards may be constrained from the age of volcanism, duration of magma storage, and magma source and plumbing system character. Zircon U-Th-Pb dating of lithic lava clasts has revealed recurrent evolved volcanism at 1.34 and 0.6 Ma, and 95 ka. The (U-Th)/He zircon cooling ages indicate that most of the EC explosive-effusive sequence erupted in a brief episode at ca. 95 ka. Additionally, uniform 238U-230Th zircon crystallisation ages suggest moderately protracted magma storage with melt present at depth for at most 103-104 years before eruption. The enriched character of zircon trace element compositions, relative to MORB, in the absence of a continental crustal signature in the oxygen isotope values (δ18O range 2.67-5.63‰), suggests the presence of an enriched component in the EC magma source. Furthermore, low δ18O zircon compositions imply assimilation of high temperature hydrothermally altered country rock by the source magma. The mineral assemblage in crystal-poor pumices indicates equilibrium storage conditions: zircon saturation and Ti-in-zircon crystallisation temperatures are consistent with alkali feldspar-melt temperatures. Significantly, zircon crystals were preserved both as macrocryst inclusions and in the groundmass of EC explosive and effusive deposits. These rocks preserve evidence of magma evolution by fractional crystallisation. This process led to pre-eruptive compositional stratification, which is evidenced in the range of whole-rock major and trace element compositions and zircon Zr/Hf values. Notably, zircon crystallisation and cooling ages derived from pumice, lava, and accidental lithic lava clasts in highly explosive pyroclastic deposits, have revealed episodes of evolved magmatism that would otherwise have gone undetected. In addition, the zircon trace element and isotope compositions, in combination with the range of crystallisation ages, evidence progressively deeper tapping of less evolved magma stored in discrete lenses. Thus, a combined zircon geochronological-geochemical approach can place constraints on the ca. 0.6 Ma recurrence of past explosive-effusive pulses of millennial to decamillennial duration and their enriched magma sources. This information is relevant for assessing hazards and informing monitoring and forecasting efforts to assist in managing associated risks for small ocean island volcanoes with particularly vulnerable populations and infrastructure.